Kepastian Hukum Hak Komunal Berdasarkan Peraturan Menteri Agraria dan Tata Ruang/Kepala Badan Pertanahan Nasional Republik Indonesia Nomor 10 Tahun 2016 ditinjau dari Hukum Pertanahan Indonesia - Aniza Dessy Daldiani (Fakultas Syariah dan Hukum UIN Sunan Ampel Surabaya, 2018)
The background of this paper is the recognition of The Customary Rights of land (Hak Ulayat) in Article 3 of Law no. 5 of 1960 on The Basic Regulations of Agrarian Principles (UUPA). The purpose of this paper is to know the legal certainty of communal rights based on Ministerial Regulation ATR/Head of BPNRI No. 10 Year 2016, with a view of the land law of Indonesia. The conclusion of this paper is that there is no legal certainty for indigenous and tribal peoples within certain areas, ie in forest areas or plantations that will propose communal rights to the land. Ministerial Regulation ATR/Head of BPNRI No. 10 Year 2016, has no legal umbrella, due to communal rights to land regulated by Ministerial Regulation ATR/Head of BPNRI No. 10 Year 2016, is not in accordance with Article 16 paragraph (1) letter h of The Basic Regulations of Agrarian Principles (UUPA), where The Basic Regulations of Agrarian Principles (UUPA) as the legal basis of Ministerial Regulation ATR/Head of BPNRI No. 10 Year 2016. In addition, the implementation of registration of communal land rights is also not in accordance with Article 9 paragraph (1) of Government Regulation no. 24/1997. Ministerial Regulation ATR/Head of BPNRI No. 10 Year 2016, which does not have a legal umbrella, of course, contradicts Hans Kelsen's theory of the level of legal norms (stufentheorie) and Adolf Merkl's Theory of legal norms always have two faces (das Doppelte Rechstanilitz)